Unsteady Viscous Flow over an Expanding Stretching Cylinder - Fang, Tie-Gang (铁钢方); Zhang, Ji (骥章); Zhong, Yong-Fang (永芳钟); Tao, Hua (华陶) (Chinese physics letters, 2011)
We study the viscous ssow over an expanding stretching cylinder. The solution is exact to the Navier-Stokes equations. The stretching velocity of the cylinder is proportional to the axial distance from the origin and decreases with time. There exists a unique solution for the ssow with all the studied values of Reynolds number and the unsteadiness parameter. Reversal flows exist for an expanding stretching cylinder. The velocity decays faster for a larger Reynolds number and a more rapidly expanding cylinder.